EDUCATIONAL STRATEGIES IN THE CONTEXT OF LEADERSHIP AND A QUANTUM PERSPECTIVE - Milka Petrova (Reviews of Modern Science, 2026)
This paper examines educational strategies through the lens of contemporary leadership and the quantum approach as a conceptual framework for management in conditions of organizational complexity. In the context of global dynamics, digital transformation, and increasing uncertainty, traditional linear models of planning and management prove insufficient for the sustainable development of educational institutions. At the core of the analysis lies the understanding that educational strategies must be long-term, adaptive, and value-oriented. They involve the formulation of a clear vision, the development of institutional culture, the integration of innovation, and the establishment of mechanisms for continuous feedback and learning. Contemporary educational strategy is not limited to administrative planning; rather, it requires strategic leadership that mobilizes human potential and creates conditions for sustainable development. The paper examines leadership as a strategic factor in shaping direction, trust, and organizational identity, while the quantum approach is presented as a metaphorical and systemic perspective emphasizing interconnectedness, the probabilistic nature of processes, and the potentiality of development. The educational institution is conceptualized as a dynamic system in which small managerial decisions can have significant impacts on culture and outcomes. An integrative conceptual framework is proposed, combining strategic management, systems thinking, and human capital development. In this context, quantum thinking supports the re-examination of managerial practices by fostering adaptability, innovation, and sustainability within the educational environment. The paper contributes to the development of an interdisciplinary approach to educational leadership and outlines perspectives for constructing strategic models aligned with the demands of the twenty-first century